Case Study : Uniform Gallery Bangi / Nur Adilla Mat Izal - Mat Izal, Nur Adilla (2020)
Uniform Gallery is a uniform store that provides various types of services including sewing clothes, printing documents and faxing a document. It is a well-known uniform store in Malaysia and has been operating for more than 20 years. The products sold by Uniform Gallery are uniforms, stationeries and books. The major problems faced by the company are seasonal consumers, limited source of reference books and maintenance of machines. The company must conduct sales frequently to attract the customers and increase the courses of reference books. Other than that, they must organize and schedule a proper time to do the maintenance of the machines in order to save cost of damages.